Alcohol use, depression, and life satisfaction among older persons in Jamaica. (12th December 2016) - Gibson, Roger C.; Waldron, Norman K.; Abel, Wendel D.; Eldemire-Shearer, Denise; James, Kenneth; Mitchell-Fearon, Kathryn
ABSTRACT: Background: We aimed to determine the prevalence of alcohol use among older Jamaicans as well as to explore among this population the relationships between alcohol use and: age, sex, depressive symptoms, and life satisfaction. Although the nature of these relationships among the proposed study population were uncertain, in other settings alcohol use has tended to decline with increasing age, occur more commonly among men than women, and show non-linear relationships with depressive symptoms and life satisfaction. Methods: Data gathered by two-stage cluster sampling for a nationally representative health and lifestyle survey of 2, 943 community-dwelling older Jamaicans, aged 60 to 103 years, were subjected to secondary analysis using the Student's t -test and χ 2 test as appropriate. Results: Current alcohol use was reported by 21.4% of the participants. It steadily declined with age and was six times more prevalent among men (37.6%) than women (6.2%). These findings were statistically significant as were associations of current alcohol use with comparatively lower levels of depressive symptoms. Current alcohol use was also more prevalent among persons who were either highly satisfied or highly dissatisfied with their lives, compared to others who had levels of life satisfaction between these two extremes. Conclusions: Current alcohol use among older Jamaicans occurs primarily among men, declines with increasing age, and is associated with a relatively low likelihood of depression. It is also associated with very high and very low levels of life satisfaction.